Polo-like kinase-activating kinases: Aurora A, Aurora B and what else? - Archambault, Vincent; Carmena, Mar (Cell cycle (Georgetown, Tex.), 2012)
The events of cell division are regulated by a complex interplay between kinases and phosphatases. Cyclin-dependent kinases (Cdks), polo-like kinases (Plks) and Aurora kinases play central roles in this process. Polo kinase (Plk1 in humans) regulates a wide range of events in mitosis and cytokinesis. To ensure the accuracy of these processes, polo activity itself is subject to complex regulation. Phosphorylation of polo in its T loop (or activation loop) increases its kinase activity several-fold. It has been shown that Aurora A kinase, with its co-factor Bora, activates Plk1 in G 2 , and that this is essential for recovery from cell cycle arrest induced by DNA damage. In a recent article published in PLoS Biology, we report that Drosophila polo is activated by Aurora B kinase at centromeres, and that this is crucial for polo function in regulating chromosome dynamics in prometaphase. Our results suggest that this regulatory pathway is conserved in humans. Here, we propose a model for the collaboration between Aurora B and polo in the regulation of kinetochore attachment to microtubules in early mitosis. Moreover, we suggest that Aurora B could also function to activate Polo/Plk1 in cytokinesis. Finally, we discuss recent findings and open questions regarding the activation of polo and polo-like kinases by different kinases in mitosis, cytokinesis and other processes.